Child maltreatment and eating disorders among men and women in adulthood: Results from a nationally representative United States sample. Issue 11 (9th October 2017) - Afifi, Tracie O.; Sareen, Jitender; Fortier, Janique; Taillieu, Tamara; Turner, Sarah; Cheung, Kristene; Henriksen, Christine A.
Abstract: Objective: Child maltreatment is associated with an increased likelihood of having mood disorders, anxiety disorders, post‐traumatic stress disorder, substance use disorders, and personality disorders, but far less is known about eating disorders. The objective of the current study was to examine the associations between child maltreatment, including harsh physical punishment, physical abuse, sexual abuse, emotional abuse, emotional neglect, physical neglect, and exposure to intimate partner violence, and eating disorders in adulthood among men and women. Method: Data were from the National Epidemiologic Survey on Alcohol and Related Conditions wave 3 (NESARC‐III) collected in 2012–2013. The sample was nationally representative of the United States adult population ( N = 36, 309). Lifetime eating disorders (anorexia nervosa [AN], bulimia nervosa [BN], and binge‐eating disorder [BED]) were assessed using diagnostic and statistical manual of mental disorders, fifth edition (DSM‐5) criteria and the alcohol use disorder and associated disabilities interview schedule‐5 (AUDADIS‐5). Results: The prevalence of any lifetime eating disorder was 1.7% (0.8% among men and 2.7% among women). All child maltreatment types were associated with AN, BN, and BED with notable differences among men and women. Overall, the types of child maltreatment with the strongest relationships with any eating disorder were sexual abuse and physical neglect among men and sexual abuse and emotional abuse among women. Discussion: Clinicians should be mindful that child maltreatment experiences are associated with increased odds of eating disorders including AN, BED, and BN. Such relationships are significant among men and women although notable gender differences in these relationships exist. Abstract word count = 248.